Waterlogging effects on growth and physiological characteristics of Azadirachta excelsa seedlings - Shukor, Nurul Nasyitah; Abdul Hamid, Hazandy; Abdu, Arifin; Ismail, Mohd Kamil (Academic Journals, 2014)
In this study the effects of waterlogging were examined on growth and physiological characteristics of Azadiractha excelsa, one of the famous indigenous tree species used for urban landscape. Forty eight seedlings about 3 year-old subjected to waterlogged for three time durations, i.e., 1, 2 and 3 weeks and at its recovery. The results had shown the highest survival percentage in two weeks of waterlogged seedlings, decreased rate in diameter, leaf area and chlorophyll content in waterlogged seedlings. In spite of all these, there was an increased in height for waterlogged treatment as compared to control. High biomass of stem was found in waterlogged treatment. There were no differences among treatments for the ratio maximum quantum efficiency of the photosystem II (Fv/Fm) and gas exchange parameters except vapour pressure deficit (VpdL). The disturbed water relation also occurred in waterlogged seedlings. Azadirachta excelsa seedlings were found to only tolerate with stress of being waterlogged up to two weeks of treatment. However, the recovery seedling leaves can still perform well in its physiological performance.